2011
DOI: 10.1128/jb.05373-11
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome of the Psychrotolerant Acidophile Acidithiobacillus ferrivorans SS3

Abstract: Acidithiobacillus ferrivorans SS3 is a psychrotolerant acidophile capable of growth in the range of 5°to 30°C (optimum, Ϸ25°C). It gains energy from the oxidation of ferrous iron and inorganic sulfur compounds and obtains organic carbon from carbon dioxide. Here, we present the draft genome sequence of A. ferrivorans SS3 that will permit investigation of genes involved in growth in acidic environments at low temperatures.Psychrotolerant acidophiles from the Acidithiobacillus genus constitute a new species, Aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
50
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 11 publications
1
50
0
1
Order By: Relevance
“…All strains grew at 10 8C (five very slowly) and three strains (including the type strain) at 5 8C. From this it was concluded that A. ferriphilus is mesophilic, but that some strains are psychrotolerant, a feature that has only previously been reported for A. ferrivorans among the ironoxidizing acidithiobacilli (Hallberg et al, 2010;Liljeqvist et al, 2011). All strains were acidophilic and grew at pH 1.8, although two strains did not grow at pH 1.5, and none at pH 1.25.…”
mentioning
confidence: 60%
“…All strains grew at 10 8C (five very slowly) and three strains (including the type strain) at 5 8C. From this it was concluded that A. ferriphilus is mesophilic, but that some strains are psychrotolerant, a feature that has only previously been reported for A. ferrivorans among the ironoxidizing acidithiobacilli (Hallberg et al, 2010;Liljeqvist et al, 2011). All strains were acidophilic and grew at pH 1.8, although two strains did not grow at pH 1.5, and none at pH 1.25.…”
mentioning
confidence: 60%
“…The Sox complex is widely distributed in bacteria (23). Genes encoding sox homologs have been found in acidophilic sulfur oxidizers Acidithiobacillus caldus (24,25) and Acidithiobacillus thiooxidans (26), the neutrophilic sulfur oxidizer Thiobacillus denitrificans (27), and the iron-and/or sulfur-oxidizer Acidithiobacillus ferrivorans (28), although the sox genes are not necessarily complete. However, homologous genes have not been found in the A. ferrooxidans ATCC 23270 genome.…”
mentioning
confidence: 99%
“…Although a suite of genes potentially encoding TQO has been identified in A. ferrooxidans (5), A. caldus (24,25), A. thiooxidans (26), and A. ferrivorans (28), the biochemical function of TQOs in these bacterial species remains elusive.…”
mentioning
confidence: 99%
“…Together with other members of the genus Acidithiobacillus (10), this bacterium has the capacity to obtain energy from inorganic sulfur compounds (ISCs) and survive in extremely high concentrations of heavy metals. A. thiooxidans is one of four members of the genus Acidithiobacillus characterized to date (6,15,16,18) whose shared metabolic and functional capabilities allow them to survive in extremely acidic environments. Little is known about the genomic and functional properties of this microbe, and most information regarding this genus comes from experimental and genome-based analyses of Acidithiobacillus ferrooxidans and Acidithiobacillus caldus (7,8,15,12).…”
mentioning
confidence: 99%